Interplay Between Exercise and Gut Microbiome in the Context of Human Health and Performance - Clauss, Matthieu; Gérard, Philippe; Mosca, Alexis; Leclerc, Marion (Frontiers in Nutrition, 2021)
Gut microbiota and exercise have recently been shown to be interconnected. Both moderate and intense exercise are typically part of the training regimen of endurance athletes, but they exert different effects on health. Moderate exercise has positive effects on the health of average athletes, such as a reduction in inflammation and intestinal permeability and an improvement in body composition. It also induces positive changes in the gut microbiota composition and in the microbial metabolites produced in the gastrointestinal tract. Conversely, intense exercise can increase gastrointestinal epithelial wall permeability and diminish gut mucus thickness, potentially enabling pathogens to enter the bloodstream. This, in turn, may contribute to the increase in inflammation levels. However, elite athletes seem to have a higher gut microbial diversity, shifted towards bacterial species involved in amino acid biosynthesis and carbohydrate/fiber metabolism, consequently producing key metabolites such as short-chain fatty acids. Moreover, rodent studies have highlighted a bidirectional relationship, with exercise impacting the gut microbiota composition while the microbiota may influence performance. The present review focuses on gut microbiota and endurance sports and how this interconnection depends upon exercise intensity and training. After pointing out the limits of the studies so far available, we suggest that taking into account the microbiota composition and its metabolic contribution to human host health could help in monitoring and modulating athletes’ health and performance. Such an integrated approach should help in the design of microbiome-based solutions for health or performance.